The formation of conjugated structure and its transformation to pseudo-graphite structure during thermal treatment of polyacrylonitrile: Effect of molecular composition and configuration. (November 2017) - Lei, Shuai; Wu, Shuai; Gao, Aijun; Cao, Weiyu; Li, Changqing; Xu, Lianghua
Three types of polyacrylonitrile (PAN) were considered in order to investigate the effect of molecular composition and configuration on the formation of conjugated structures during stabilization and the conversion of that to pseudo-graphite sheets after carbonization. The stabilization process was performed in an inert or oxidative atmosphere with a temperature ramp from 180°Cto 280°C. The thermal behavior was studied by differential scanning calorimetry, and the change of chemical groups and conjugated structures was detected by in situ measurement of infrared (Fourier transform infrared) and ultraviolet–visible spectroscopy, respectively. The carbonization process of the stabilized samples was performed using a thermogravimetric analyzer under nitrogen atmosphere in the temperature range of 150°C–1200°C, and Raman spectra were applied to study the pseudo-graphite sheets of the residuals. It is suggested that the introduction of comonomer or the improvement of the isotactic regularity of the polymer chain are helpful to promote the stabilization reactions and accelerate the formation of conjugated structures rather than the extent of conjugation during stabilization in nitrogen. Moreover, they are also beneficial to obtain higher degree of graphitization and larger size of the pseudo-graphite sheets with less structural defects after carbonization. While stabilization is performed in air, atactic PAN copolymer has the highest extent of stabilization among these three PAN samples, but they are extremely close. PAN samples with comonomer or higher isotacticity still show a little advantage in the formation speed of the conjugated structures. After carbonization, PAN with higher isotacticity has the highest carbon yield and graphitization degree and the largest size of pseudo-graphite sheets with least structural defects. In addition, the presence of oxygen during stabilization is contributory to increase the extent of stabilization and generate some bigger conjugated structures, which leads to obtain higher graphitization degree and larger size of pseudo-graphite sheets, but it also brings more structural defects.